Efeitos da terapia manipulativa e do treinamento interativo com games na percepção da dor crônica, capacidade funcional e marcadores periféricos bioquímicos de idosas - Pasqualotti, Pablo (2016)
This work aimed to analyze the population of elderly participants in social groups in the city of Passo Fundo, to understand who these people are, their needs, advantages and shortcomings. Nestre paper presents two secondary objectives envisioned in each of the scientific production; production I the objective was to verify the relationship between body mass index (BMI) and use of medicines for arthritis arthrosis this elderly population; production II the objective was to verify the effects of manipulative therapy and interactive training games in the perception of chronic pain and elderly peripheral biochemical markers. The study of the production I is a cross-sectional, descriptive / analytical and population, while the study of production II is the randomized clinical type. The study population consists of adults and elderly participants in social groups of the Coordination of Elderly Care (DATI) of Passo Fundo / RS. To address these assessments, the dissertation was divided in two scientific publications that are equivalent to two distinct moments of research. At first production I aimed to investigate the relationship between body mass index and use of medication for arthritis / osteoarthritis. According to estimates of the World Health Organization, between 2010 and 2050 the number of older people in developing countries will double. At least 85% of people aged over 70 years have radiological diagnosis of osteoarthritis (arthrosis), while 6% of Brazil's population has some rheumatic disease. The population is composed of 850 adults and the elderly. The participants answered a questionnaire with 31 questions containing sociodemographic variables, use of medication, pain perception, nutritional status and use of technologies. The results showed a significant difference between the mean BMI of people who take medication (28.8) and those who do not take (27.1). In the second phase the aim of production II was to investigate the effects of spinal manipulation and interactive training game in oxidative stress and pain perception of older people. The reactive oxygen species (ROS) have been suggested as possible mediators of neuropathic pain. Some neuromusculoskeletal disorders affect neural function through the release of pro-inflammatory substances and pro-oxidative, with great chances of pain chronicity. This sample consisted of 27 elderly people who were randomly divided into three groups: a control group that received no intervention; group 2 received joint manipulation once a week over 14 weeks; Group 3 held interactive training games twice semanae received joint manipulation once a week, both interventions over 14 weeks. For the analysis was used ANOVA, Wilcoxon test and the Student's t-test. The significance level used in the tests was p ≤ 0.05. Group 1 showed no significant difference in any parameter evaluated. Group 2 decreased perception of pain (p = 0.027) and the levels of TBARS (p = 0.019). Group 3 showed reduced perception of pain (p = 0.016), but no differences in markers of oxidative stress. It follows from the production I, people who take medicine for arthritis / osteoarthritis have BMI index higher than compared to those who do not make use of these drugs, this relation of the fact that the overweight influence the mechanical overload of joints, making symptomatic arthritis / osteoarthritis. According II production results, it is concluded that the treatment of muscular pains by manual therapy causes reduction in oxidative stress levels and analgesia. Manual therapy when associated with physical activity performed by gaming reduces pain but not the levels of oxidative stress.